2020
DOI: 10.1093/ajcn/nqaa148
|View full text |Cite
|
Sign up to set email alerts
|

Association between anemia and household water source or sanitation in preschool children: the Biomarkers Reflecting Inflammation and Nutritional Determinants of Anemia (BRINDA) project

Abstract: Background The associations between anemia and household water source and sanitation remain unclear. Objectives We aimed to assess the associations between anemia and household water source or sanitation in preschool children (PSC; age 6–59 mo) using population-based surveys from the Biomarkers Reflecting Inflammation and Nutritional Determinants of Anemia (BRINDA) project. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
(34 reference statements)
6
8
0
1
Order By: Relevance
“…Our findings suggest that subclinical presence of specific invasive enteropathogenic bacteria, particularly EAEC and EIEC/Shigella, may contribute to anemia in young children. Prior literature has found that poor water and sanitation are associated with anemia among young children living in LMICs [48,49], with the hypothesis that exposure to enteropathogens underlies this relationship [14]. By demonstrating an association between certain enteropathogens and anemia, our results lend direct evidence to support this hypothesis.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our findings suggest that subclinical presence of specific invasive enteropathogenic bacteria, particularly EAEC and EIEC/Shigella, may contribute to anemia in young children. Prior literature has found that poor water and sanitation are associated with anemia among young children living in LMICs [48,49], with the hypothesis that exposure to enteropathogens underlies this relationship [14]. By demonstrating an association between certain enteropathogens and anemia, our results lend direct evidence to support this hypothesis.…”
Section: Discussionsupporting
confidence: 77%
“…However, EIEC/Shigella was associated with both iron deficiency and anemia, and children positive for EIEC/Shigella exhibited 5 g/L lower Hb concentrations on average than children without EIEC/Shigella. Several recent studies have linked indicators of enteropathogen exposure, such as poor water and sanitation conditions [48,49] and biomarkers of EED [28,29,31], to lower hemoglobin concentrations and anemia in young children, prompting the hypothesis that enteropathogen infections are directly linked to anemia [14]. Analysis of the MAL-ED (Etiology, Risk Factors, and Interactions of Enteric Infections and Malnutrition and the Consequences for Child Health) multi-site birth cohort study indeed demonstrated that the mean number of different parasitic, viral, and bacterial enteropathogens detected in both diarrheal and nondiarrheal stools across children's first 24 months of life was associated with lower hemoglobin concentrations [23].…”
Section: Plos Onementioning
confidence: 99%
“…For example, a multi-country study found an association between improved water access and lower risk of stunting [ 17 ]; however, a study conducted in Nepal failed to identify this association [ 18 ]. The association between water access and anemia was not established in multi-country pooled samples, however, it was significant in certain countries (e.g., Laos and Burundi) [ 19 , 20 ]. Furthermore, the extent to which other interventions can mitigate environmental risks is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…En el estudio se puede denotar un variable explicativa importante como la disposición y acceso al agua en los niños tamizados. Diversas investigaciones (13)(14)(15) demuestran la relación directa entre la fuente de agua, saneamiento y anemia. Siendo el acceso al agua mejorada un factor protector para el desarrollo infantil óptimo.…”
Section: Discussionunclassified